Restoration of normal febrile response to endotoxin in pyrogen-tolerant rabbits by injection with human beta interferon. - Kawasaki, H (1987)
Early-phase pyrogen tolerance was induced in rabbits by two consecutive daily injections of 125 ng of endotoxin per kg of body weight. The second injection of the same dose of endotoxin evoked only a monophasic fever with a peak response 1.5 h after the injection; no second peak was observed. The rabbits were released from the tolerance to develop a typical biphasic fever by an injection of 125 ng of endotoxin along with human beta interferon (HuIFN-beta), although the tolerance-inducing amount of endotoxin alone could not. The profile of the febrile response of tolerant rabbits injected with both endotoxin and HuIFN-beta could not be distinguished from that of normal rabbits. There was no essential difference between natural and recombinant HuIFN-beta in breaking tolerance. Heat-stable (70 degrees C, 30 min) endogenous pyrogen or tumor necrosis factor was increased significantly in concentration in the serum of tolerance-broken rabbits. These results suggest that HuIFN-beta stimulates the production of tumor necrosis factor in tolerant rabbits to elicit the second peak of febrile response.